2008
DOI: 10.1039/b711910k
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic complexes as anion hosts

Abstract: New anion hosts have been accessed using cationic organometallic fragments with sufficient kinetic stability as geometry-organizing cores, simple ditopic ligands featuring hydrogen bond donor groups, and the inert, low interacting, lipophilic BAr9 4 anion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(25 citation statements)
references
References 74 publications
0
24
0
Order By: Relevance
“…The enhanced solubility of the compounds relative to the free ligands is attributable to the blocking of the hydrogen-bonding acceptor atoms of the ligands (N atoms) after coordination and, in the cationic complexes, to the cation−cation repulsion, as well as the anion interposition, all of which contribute to disruption of the intermolecular hydrogen bonds that build the strong selfassociation in the crystal network of the free ligands. 27 Nevertheless, the solubility values show a strong dependence on the counterion, the overall charge of the complex (related to the formal charge of the ligands) and the arene identity. The chloride salts are much more soluble in water than their BF 4 − counterparts, in agreement with the trend observed in the literature for other families of ruthenium(II) arene complexes, which is explained as a result of the high hydration energy attributed to the Cl − anion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The enhanced solubility of the compounds relative to the free ligands is attributable to the blocking of the hydrogen-bonding acceptor atoms of the ligands (N atoms) after coordination and, in the cationic complexes, to the cation−cation repulsion, as well as the anion interposition, all of which contribute to disruption of the intermolecular hydrogen bonds that build the strong selfassociation in the crystal network of the free ligands. 27 Nevertheless, the solubility values show a strong dependence on the counterion, the overall charge of the complex (related to the formal charge of the ligands) and the arene identity. The chloride salts are much more soluble in water than their BF 4 − counterparts, in agreement with the trend observed in the literature for other families of ruthenium(II) arene complexes, which is explained as a result of the high hydration energy attributed to the Cl − anion.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The {Mo(η 3 ‐allyl)(CO) 2 } metal fragments were selected because previous studies have shown that [Mo(η 3 ‐allyl)(CO) 2 L 3 ][BAr′ 4 ] derivatives, where L 3 represents three monodentate ligands or a tridentate ligand that occupies three fac ‐capping positions, could be straightforwardly prepared and are relatively stable 7. Tetraarylborate BAr′ 4 (Ar′=3,5‐bis(trifluoromethyl)phenyl) was chosen as the counteranion of the cationic complex hosts to minimize the competition with the anionic guests 5e,f…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] One family of metal complexes that has shown considerable promise in the design of emissive sensors has been that of the fac-rhenium(I) tricarbonyl diimine fragment, where the sixth coordination site can accommodate either a neutral ligand to give a monovalent cation, or a halide to provide a neutral complex. Anion recognition has been observed in a variety of complexes, [34][35][36][37][38][39][40] and previously we have…”
Section: Introductionmentioning
confidence: 99%